Early results of multicenter phase II trial of perioperative oxaliplatin and capecitabine without radiotherapy for high-risk rectal cancer: CORONA I study. Issue 6 (June 2016) - Kamiya, T.; Uehara, K.; Nakayama, G.; Ishigure, K.; Kobayashi, S.; Hiramatsu, K.; Nakayama, H.; Yamashita, K.; Sakamoto, E.; Tojima, Y.; Kawai, S.; Kodera, Y.; et al.
Abstract: Backgrounds: Perioperative introduction of developed chemotherapy into the treatment strategy for locally advanced rectal cancer (LARC) may be a promising option. However, the most prevalent treatment for high-risk LARC remains preoperative chemoradiotherapy (CRT) in Western countries. Patients and methods: A phase II trial was undertaken to evaluate safety and efficacy of perioperative XELOX without radiotherapy (RT) for patients with high-risk LARC. Patients received 4 cycles of XELOX before and after surgery, respectively. Primary endpoint was disease-free survival. Results: We enrolled 41 patients between June 2012 and April 2014. The completion rate of the preoperative XELOX was 90.3%. Twenty-nine patients (70.7%) could start postoperative XELOX, 15 of these patients (51.7%) completed 4 cycles. Allergic reaction to oxaliplatin was experienced by 5 patients (17.2%) during postoperative XELOX. One patient received additional RT after preoperative XELOX. Consequently, the remaining 40 patients underwent primary resection. Major complications occurred in 6 of 40 patients (15.0%). Pathological complete response (pCR) rate was 12.2%, and good tumor regression was exhibited in 31.7%. N down-staging (cN+ to ypN0) and T down-staging were detected in 56.7% and 52.5%, respectively. Clinical T4 tumor was a predictor of poor pathological response (p < 0.001). Conclusions: We could show the favorable pCR rate after preoperative XELOX alone. However, the T and N down-staging rate was likely to be insufficient. When tumor regression is essential for curative resection, the use of preoperative CRT is likely to be recommended. For patients with massive LN metastasis, the additional Bev to NAC might be a promising option.